DISKRIMINASI KELAS DAN GENDER TERHADAP PEREMPUAN BALI DALAM NOVEL TARIAN BUMI KARYA OKA RUSMINI - Rejo, Uman (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
This paper discusses class and gender discrimination in Tarian Bumi, a novel written by Oka Rusmini (2007). Class and gender discrimination can be seen through the differences in actions, statuses, and positions between the brahmana class and the sudra class, and between the male and female characters, not only in domestic issues, but also in public issues. The differences in actions, statuses, and positions are manifested in the oppression of the lower class (sudra and female) by the stronger class (brahmana and male). This paper adopts a feminist approach to investigate the class and gender discrimination as found in the novel.Keywords: Teori Feminis, Diskriminasi Kelas, Diskriminasi Gender, Perempuan Bali